Effect of price limits: initial public offerings versus seasoned equities - Kim,Yong H.; Yang,Jimmy (International Review of Finance, 2009)
In this paper, we examine the effect of price limits on initial public offerings (IPOs) using Taiwanese data. On average, it takes 6.24 days for IPOs to reach their equilibrium prices in the presence of a 7% price limit. We compare IPOs with their industry- and size-matched seasoned equities (MSEs) and observe higher volatility levels on subsequent days for IPOs than for MSEs. However, the higher volatility decays within 2 days. Lower price limits interfere with trading and lead to higher trading activity on subsequent days for IPOs than for MSEs. We also observe delayed price discovery for both IPOs and MSEs. Overall, our results provide evidence about the effect of price limits on IPOs and generate important regulatory implications for countries imposing price limits on IPOs.
Keywords: Finance